Multispectral Live‐Cell Imaging. Issue 1 (14th May 2018) - Cohen, Sarah; Valm, Alex M.; Lippincott‐Schwartz, Jennifer
Abstract: Fluorescent proteins and vital dyes are invaluable tools for studying dynamic processes within living cells. However, the ability to distinguish more than a few different fluorescent reporters in a single sample is limited by the spectral overlap of available fluorophores. Here, we present a protocol for imaging live cells labeled with six fluorophores simultaneously. A confocal microscope with a spectral detector is used to acquire images, and linear unmixing algorithms are applied to identify the fluorophores present in each pixel of the image. We describe the application of this method to visualize the dynamics of six different organelles, and to quantify the contacts between organelles. However, this method can be used to image any molecule amenable to tagging with a fluorescent probe. Thus, multispectral live‐cell imaging is a powerful tool for systems‐level analysis of cellular organization and dynamics. © 2018 by John Wiley & Sons, Inc.